3D porous poly(ε-caprolactone)/58S bioactive glass–sodium alginate/gelatin hybrid scaffolds prepared by a modified melt molding method for bone tissue engineering. (15th December 2018) - Mao, Daoyong; Li, Qing; Li, Daikun; Tan, Ya; Che, Qijun
Abstract: Natural-synthetic hybrid scaffold has attracted great interest due to its synergistic effect on load-bearing bone reconstruction. Herein, sodium alginate (SA)/gelatin (Gel) composite were combined with poly(ε-caprolactone)/58S bioactive glass (PCL/BG) composite to construct natural-synthetic hybrid scaffold by a modified melt molding method. Our results showed that the SA/Gel microspheres used as porogen remained inside the scaffold, which had potential benefits for cell adhesion. The PCL/BG composite acted as the struts. The incorporation of BG resulted in a significant increase in the mechanical properties of the scaffold. Specially, HS-3 scaffold showed a compressive strength of 1.44 ± 0.02 MPa falling within the range of values reported for the cancellous bone. In addition, the presence of BG improved wettability and biodegradability of the scaffold, thus potentially enhancing osteointegration. In conclusion, the PCL/BG–SA/Gel hybrid scaffold with improved mechanical properties and potential cytocompatibility are promising biomaterials for bone repair. Graphical abstract: Highlights: The hybrid scaffolds were fabricated by a modified melt molding method. Algiante/gelatin microspheres as porogen potentially improved cytocompatibility. Scaffold properties were tuned by the content of bioactive glass. The compressive strength reached 1.44 MPa suitable for cancellous bone repair.